We are given the following two functions
![\begin{gathered} f(x)=(1)/(x-4) \\ g(x)=(1)/(x)-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rds9wmxvy589rgan2emmoq7fz9ke7gqdr8.png)
Let us evaluate the functions on the given points.
a. f(1/4)
Substitute x = 1/4 into the function f(x)
![f((1)/(4))=(1)/((1)/(4)-4)=(1)/((1-4\cdot4)/(4))=(1)/((1-16)/(4))=(1)/((-15)/(4))=-(4)/(15)](https://img.qammunity.org/2023/formulas/mathematics/college/j63samkaxnzowi6kw9lebdn5tjw7drh5yy.png)
Therefore, f(1/4) = -4/15
b. g(1/4)
Substitute x = 1/4 into the function g(x)
![g((1)/(4))=(1)/((1)/(4))-3=4-3=1](https://img.qammunity.org/2023/formulas/mathematics/college/zzfmtkgjz0dk5jmhesrzcakbokenvb4gdr.png)
Therefore, g(1/4) = 1
c. f(-1/3)
Substitute x = -1/3 into the function f(x)
![f(-(1)/(3))=(1)/(-(1)/(3)-4)=(1)/((-1-3\cdot4)/(3))=(1)/((-1-12)/(3))=(1)/((-13)/(3))=-(3)/(13)](https://img.qammunity.org/2023/formulas/mathematics/college/2xjtzd4utg5rjgbiagvff051nlwuuhh9he.png)
Therefore, f(-1/3) = -3/13
d. g(-1/3)
Substitute x = -1/3 into the function g(x)
![g(-(1)/(3))=(1)/(-(1)/(3))-3=-3-3=-6](https://img.qammunity.org/2023/formulas/mathematics/college/5630p2b0ab9cbm0wmmdl1w4mfgz4fylue1.png)
Therefore, g(-1/3) = -6